Land reform in Japan - "Dore, R.P." (London, 1984)
This classic study of post war Japan is again available and like Education in Tokugawa Japan with a newly written Preface. At the time of its first publication in 1959, it was hailed as a masterly and authoritative account of this crucial and revolutionary measure of land reform, initiated by the occupying powers. It is based upon Japanese written sources and also upon Professor Dore's personal knowledge of Japanese farming life and village communities. It stands as one of the most highly informed accounts of Japanese culture and its economy.
Keywords: Land reform Japan History 20th Century